2013
DOI: 10.2308/acch-50502
|View full text |Cite
|
Sign up to set email alerts
|

How Does the Strength of the Financial Regulatory Regime Influence Auditors' Judgments to Constrain Aggressive Reporting in a Principles-Based Versus Rules-Based Accounting Environment?

Abstract: SYNOPSIS: With the movement toward adoption of International Financial Reporting Standards (IFRS) worldwide, a question arises as to whether the adoption of a principles-based approach, such as IFRS, will ultimately result in higher-quality financial reporting. This issue is particularly relevant because, even though for now the SEC is not adopting IFRS, the securities markets and the SEC still need to ponder the implications of a decision that may lead to the ultimate adoption of, or at least s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
70
2
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(82 citation statements)
references
References 54 publications
2
70
2
8
Order By: Relevance
“…Recent studies on this topic have found that under principlesbased accounting standards, auditors are more likely to constrain aggressive reporting (Cohen, Krishnamoorthy, Peytcheva, & Wright, 2013) and increase process accountability, epistemic motivation, and demand for evidence (Peytcheva, Wright, & Majoor, 2014). Our study adds to prior research by investigating how auditors play their role in the implementation of principles-based versus rules-based accounting standards in China, which is an environment where auditors have experienced recent changes to accounting standards.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…Recent studies on this topic have found that under principlesbased accounting standards, auditors are more likely to constrain aggressive reporting (Cohen, Krishnamoorthy, Peytcheva, & Wright, 2013) and increase process accountability, epistemic motivation, and demand for evidence (Peytcheva, Wright, & Majoor, 2014). Our study adds to prior research by investigating how auditors play their role in the implementation of principles-based versus rules-based accounting standards in China, which is an environment where auditors have experienced recent changes to accounting standards.…”
Section: Introductionmentioning
confidence: 85%
“…The influence of the type of accounting standards on auditing varies from country to country since the strength of the financial regulatory regime is significantly different across countries (Ball, 2006). Part of the mechanism behind this may be that auditors' efforts, accountabilities, and focus may vary under principlesbased versus rules-based accounting standards based on the strength of the financial regulatory regime (Cohen et al, 2013). Part of the mechanism behind this may be that auditors' efforts, accountabilities, and focus may vary under principlesbased versus rules-based accounting standards based on the strength of the financial regulatory regime (Cohen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 This could occur, for example, if international auditors standardize practice advice across jurisdictions or if auditors believe that the bright-line criteria fairly reflect the principle. Cohen et al (2013) find, in an experimental setting with bright-line tests, that auditors are more likely to require capitalization when the standard contains a professional judgement clause. Nelson et al (2002) report that auditors believe that firms use transaction structuring less under principles-based standards but also note that less precise standards can create room for auditor-client negotiation to achieve client reporting goals.…”
mentioning
confidence: 83%
“…In particular, auditors are typically alleged of having conspired with managers to manipulate financial reports because the audited financial statement of an audit client represents the outcome of an audit process determined through "auditor-client negotiation" (Gibbins, Salterio & Webb 2001). Therefore, since one of the primary duties of an auditor is to curtail the aggressive reporting of managers (Cohen et al 2013), the audited financial statement captures the level of reporting discretion and the earnings quality that an auditor's judgement permits his or her client (Antle & Nalebuff 1991). Accrual quality is a metric that is frequently used by researchers to capture the extent of an auditor's tolerance of a client's opportunistic reporting behaviour (DeFond & Zhang 2014;Jamal & Tan 2010).…”
Section: Introductionmentioning
confidence: 99%